THE METHOD OF ENSURING THE RELIABILITY OF SINGLE-CHANNEL WIRELESS TELECOMMUNICATION NETWORKS UNDER THE CONDITION OF MINIMIZING THE AMOUNT OF RESOURCES INVOLVED - Kozlovskyi, Valerii; Zalevskyi, Bogdan (Science-based technologies, 2023)
Modern telecommunication networks play an increasingly important role in the development of all channels of interaction in society and the development of economic relations and are constantly being put forward for more and more diverse uses. Subscribers of any modern telecommunication networks expect from them, first of all, a stable and reliable process of transmitting useful data in the conditions of the entire spectrum of various interferences, disturbances and failures of functioning. One of the elements of ensuring a stable and reliable process of transmitting useful data is the task of maintaining the reliability of single-channel wireless telecommunication networks. The article analyzes and determines the most optimal topological schemes for the construction of a telecommunications network in terms of resource minimization, substantiates the method of ensuring reliability in relation to the presented schemes, and develops a method of ensuring the reliability of a single-channel wireless telecommunications network reduced to optimal topological schemes by construction. It has been established that topological schemes "point-to-point", "bus", "tree" is the most optimal for construction according to the criterion of minimizing the costs of their construction. It is substantiated that the most accepted method of ensuring the reliability of topological schemes for the construction of single-channel wireless telecommunication networks is the redundancy method. A methodical approach to ensuring the reliability of the telecommunications network has been developed, which involves a comprehensive assessment of all factors, a procedure for the equivalent reduction of complex elements and schemes of the topological construction of the telecommunications network to one equivalent element with a corresponding reliability indicator, and a procedure for vertical and horizontal decomposition of the topological scheme into elementary subsystems. The results presented in the article can be used in the development of new and improvement of existing single-channel wireless telecommunication networks in the direction of ensuring their reliable and error-free operation.